Vestibular thalamus: Two distinct graviceptive pathways. (12th January 2016) - Baier, Bernhard; Conrad, Julian; Stephan, Thomas; Kirsch, Valerie; Vogt, Thomas; Wilting, Janine; Müller-Forell, Wibke; Dieterich, Marianne
Abstract : Objective: To determine whether there are distinct thalamic regions statistically associated with either contraversive or ipsiversive disturbance of verticality perception measured by subjective visual vertical (SVV). Methods: We used modern statistical lesion behavior mapping on a sample of 37 stroke patients with isolated thalamic lesions to clarify which thalamic regions are involved in graviceptive otolith processing and whether there are distinct regions associated with contraversive or ipsiversive SVV deviation. Results: We found 2 distinct systems of graviceptive processing within the thalamus. Contraversive tilt of SVV was associated with lesions to the nuclei dorsomedialis, intralamellaris, centrales thalami, posterior thalami, ventrooralis internus, ventrointermedii, ventrocaudales and superior parts of the nuclei parafascicularis thalami. The regions associated with ipsiversive tilt of SVV were located in more inferior regions, involving structures such as the nuclei endymalis thalami, inferior parts of the nuclei parafascicularis thalami, and also small parts of the junction zone of the nuclei ruber tegmenti and brachium conjunctivum. Conclusions: Our data indicate that there are 2 anatomically distinct graviceptive signal processing mechanisms within the vestibular network in humans that lead, when damaged, to a vestibular tone imbalance either to the contraversive or to the ipsiversive side.